2017
DOI: 10.1373/clinchem.2017.274175
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Confirmation, and Replication of Novel Urinary MicroRNA Biomarkers in Lupus Nephritis and Diabetic Nephropathy

Abstract: BACKGROUND The prevalence of chronic kidney disease (CKD) is increasing, leading to significant morbidity and mortality. Kidney biopsy remains the gold standard for diagnosing the underlying etiology of CKD, but the procedure carries complication risks. The aim of this study was to identify novel noninvasive biomarkers correlating with kidney function and histopathology in biopsyproven CKD patients. METHODS We profiled 2402 urinary microRNAs (miRNAs) to identify and confirm differentially expressed miRNAs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 38 publications
0
63
0
2
Order By: Relevance
“…However, in diabetic nephropathy, miR-4532, miR-1915-3p and miR-2861 were downregulated and associated with estimated glomerular filtration rate and interstitial fibrosis/tubular atrophy. This study for the first time showed that miRNAs can be used as biomarkers to distinguish LN and diabetic nephropathy [87].…”
Section: Extracellular Rna and Organ Involvement In Slementioning
confidence: 78%
See 1 more Smart Citation
“…However, in diabetic nephropathy, miR-4532, miR-1915-3p and miR-2861 were downregulated and associated with estimated glomerular filtration rate and interstitial fibrosis/tubular atrophy. This study for the first time showed that miRNAs can be used as biomarkers to distinguish LN and diabetic nephropathy [87].…”
Section: Extracellular Rna and Organ Involvement In Slementioning
confidence: 78%
“…exRNAs may take parts in the process of SLE and some of them can be used as diagnostic tool for SLE. lnc-DC ↓ [82] miR-22 ↓ Lupus nephritis [76] miR-15b ↓ [76] miR-151a-3p ↓ [84] miR-130b ↓ [86] miR-5571-5p ↓ [87] miR-766-3p ↓ [87]…”
Section: Discussionmentioning
confidence: 99%
“…Although most miRNAs are kept in cells, there are still plenty of miRNAs found in extracellular environment, such as serum, urine and breast milk. MiRNAs in urine have been exploited as a potential biomarker to diagnose multiple diseases like urinary system cancer, kidney injury and diabetes, and they have already been demonstrated many advantages as stable and noninvasive biomarkers for early stage detection 3134 . However, the traditional method to extract miRNA from urine is cumbersome and costly.…”
Section: Discussionmentioning
confidence: 99%
“…215 215 Studies reported that the three decreased miR-NAs are related to increased levels of IFTA and tubulointerstitial inflammation, suggesting the role of these miRNAs in fibrosis formation in DN. 219 Notably, studies reported that miR-192 is increased in the early stage of DN patients but it is decreased in the late stage, 220 Among others, the detection of miRNAs in urine may act as a fresh non-invasive approach for diagnosis and dynamic monitoring of diabetic microvascular complication to especially improve the prediction, treatment and prognosis without the need for invasive diagnostic or radiological procedures.…”
Section: Diabetic Microvascular Complicationmentioning
confidence: 99%